WALES-WALES DALAM TRADISI KEMATIAN DUSUN MELOAN DESA SIDOREJO KABUPATEN MALANG - Putri, Rindy Dwi Mentari; Amalia, Rizka Fatna; Tasyah, Salsabilla Divana; Sweliyantri, Vio; Wachidah, Windi Nurul; Fatanti, Megasari Noer; Fatah, Zainal (Universitas Tanjungpura, 2022)
This study aims to discuss the Wales-wales system in the Javanese tradition of death, especially in East Java. In the community structure of Dusun Melon, Desa Sidorejo, Malang Regency, the Wales-wales tradition (returning the favor) is known as an activity to help residents who are experiencing death. This tradition has been carried out for generations and is thought to be able to become the social glue of the lives of the residents of Dusun Meloan, Desa Sidorejo. In the activities of Wales-wales there is a reciprocal relationship that is mutualism between one individual and another, thus fostering social cohesion that persists to this day. This study uses a qualitative approach with data collection techniques through observation and intermittent interviews with informants. Through Talcott Parson's AGIL concept, this study seeks to answer problems related to (1) how the Welsh-Wales tradition has survived to this day and (2) the extent to which the local community has adapted to the Welsh-Wales tradition in their social life. Based on the results of field data analysis, at least this research yields several points, namely (1) the Wales-wales tradition is a form of social communication in rural communities, especially Sidorejo Village, Malang Regency; (2) the Welsh-Wales tradition became the glue for the social relations of the Sidorejo Village community when the Covid-19 pandemic hit; and (3) the Wales-wales tradition is a local value that is agreed to be a principle of life and must be preserved as part of efforts to strengthen social relations in rural communities.